Association of a CHEK2 somatic variant with tumor microenvironment calprotectin expression predicts platinum resistance in a small cohort of ovarian carcinoma - Izabela Ferreira Gontijo de Amorim; Carolina Pereira de Souza Melo; Ramon de Alencar Pereira; Sidnéa Macioci Cunha; Thalía Rodrigues de Souza Zózimo; Fábio Ribeiro Queiroz; Iago de Oliveira Peixoto; Luciana Maria Silva Lopes; Laurence Rodrigues do Amaral; Matheus de Souza Gomes; Juliana Almeida Oliveira; Eduardo Batista Cândido; et al. (PLoS ONE, 2025)
High-grade serous ovarian cancer (HGSOC) low overall survival rate is often attributed to platinum resistance. Recent studies suggest that the tumor associated-microenvironment (TME) is a determining factor in malignant tumor progression and DNA damage plays a crucial role in this process. Here, we sought to identify platinum resistance biomarkers associating the TME immune profile and the mutational landscape of the homologous repair pathway genes with the HGSOC patients prognosis and response to chemotherapy. Using a decision tree classifier approach, we found that platinum resistant (PR) patients were characterized by the presence of a novel deep intronic variant, the CHEK2 c.319+ 3943A > T, and higher L1 expression (p =  0.016), (100% accuracy). Chek2 protein is an important component of DNA repair and L1, also known as calprotectin, is one component of the neutrophil extracellular traps (NETs) during inflammation, previously suggested as a key contributor to the metastatic process in HGSOC. Also, PD-L2 levels were significantly higher in PR patients positive for this CHEK2 variant (p =  0.048), underscoring the need to explore its potential therapeutic role for this cancer. Our results suggest an interplay between TME and DNA repair variants that results in a multifactorial nature of HGSOC resistance to platinum chemotherapy.